Pengaruh Suplementasi Minyak Ikan Lemuru Terproteksi dan L-Carnitin Dalam Ransum Terhadap Kecernaan Bahan Kering dan Bahan Organik Pada Pakan Sapi Perah Laktasi - Sudibya, Sudibya; Akbar, Kharunia Rezki; Sabar, Wara Pratitis; Riyanto, Joko (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2017)
This study aimed to determine the effect of supplementation lemuru fish oil protected and L-carnitine on digestibility value of lactating dairy cows. The materials used were 12 lactating dairy cows with average body weight 400 ± 5 kg. The study design was a randomized block design with 4 treatments and each treatment consisting of 3 blocks, each block contains one period of lactation dairy cows. Treatments were P0 = 45% rice straw + 55% concentrate; P1 = 15% rice straw + 30% fermented rice straw + 55% concentrate; P2 = 15% rice straw + 30% fermented rice straw + 55% concentrate + 1000 ppm L-carnitine; and P3 = 15% rice straw + 30% rice straw fermented rice straw + 55% concentrate + 1000 ppm L-carnitine + 4% protected lemuru fish oil. . The results of variance analysis showed that supplementation protected lemuru fish oil and L-carnitine in the diet rice straw fermentation was high significantly increased (P <0.01) on dry matter intake, consumption as well as dry matter digestibility and digestibility of organic matter in lactating dairy cows. It could be concluded that supplementation protected lemuru fish oil and L-carnitine in the diet of rice straw fermented able to reduce the consumption of dry matter and organic matter and increase the value of dry matter and organic matter digestibility.